Tabuik, Warisan Budaya Islam Sumatera Barat - Inda Violina; Isrina Siregar; Supian Ramli (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Tabuik is a tradition inherited from the people of Kota Pariaman. The tabuik tradition is a ceremony to commemorate the death of Husein bin Ali who died while fighting in Karbala. Tabuik is one of the cultural heritages in the form of a ritual tradition that has developed in Pariaman since two centuries ago. Tabuik is a ceremony or celebration to commemorate the death of the Prophet Muhammad's grandson, Husein bin Ali, who died during the war in Karbala, but later developed into a cultural performance that became the hallmark of Pariaman after the inclusion of Minangkabau cultural elements. many parties were involved in the success of the tabuik celebration, namely the community and the Pariaman City government. The method used in this study is a descriptive research method in the form of a literature study, which emphasizes an explanation of the history of the tabuik tradition to the implementation of the tabuik tradition. Tabuik has been developing in Pariman since two centuries ago, but it is still being preserved today. Tabuik is the Islamic cultural heritage of West Sumatra, especially Pariaman.